Effectiveness of Foot Exercise on Improving Ankle-Brachial Pressure Index (ABPI) in Young Adults at Risk of Peripheral Artery Disease (PAD) - Aminuddin, Muhammad; Rahmadhani, Siti; Alhawaris (Universitas STRADA Indonesia, 2026)
Background: Peripheral artery disease (PAD) is a vascular complication associated with cardiovascular disease or diabetes mellitus and, if not adequately managed, may progress to severe morbidity and increased mortality risk. The prevalence of PAD, based on an Ankle-Brachial Pressure Index (ABPI) value of ≤ 0.89, among students of the Faculty of Medicine at Mulawarman University is approximately 44.7%. Foot exercise is a simple physical activity that, when performed sequentially and regularly, can enhance peripheral blood circulation and improve lipid metabolism, including increasing HDL cholesterol and reducing total cholesterol and triglyceride levels. Purpose: To evaluate the effectiveness of foot exercise in improving the Ankle-Brachial Pressure Index (ABPI) among young adults at risk of peripheral arterial disease. Methods: This study employed a quasi-experimental design using a pre-test and post-test non-equivalent control group approach. Forty respondents with an ABPI value of ≤ 0.89 were randomly assigned to two groups (intervention and control), with 20 participants in each group. The intervention group performed foot exercises three times per week for one month, while the control group did not receive any intervention. Data analysis was conducted using the paired t-test. Results: The mean ABPI value increased after foot exercise, from 0.75 (SD = 0.83) to 0.97 (SD = 0.70). This difference was statistically significant (p < 0.05). Conclusion: Foot exercise is effective in increasing ABPI values among young adults at risk of peripheral artery disease (PAD).